RETRACTED: LINC00346 Acts as a Competing Endogenous RNA Regulating Development of Hepatocellular Carcinoma via Modulating CDK1/CCNB1 Axis - Jin, Jinglan; Xu, Hongqin; Li, Wanyu; Xu, Xiaotong; Liu, Huan; Wei, Feng (Frontiers in Bioengineering and Biotechnology, 2020)
Hepatocellular carcinoma (HCC) is one of the important types of liver cancer. LncRNA is an important regulatory factor that regulates many biological processes such as tumor cells during tumorigenesis and metastasis. LINC00346 has been associated with various types of liver cancer, but its role and regulatory mechanism in HCC remain unclear. In our study, we found the LINC00356-miR-199a-3p-CDK1 /CCNB1 axis through bioinformatics analysis. The expressions of LINC00356, miR-199a-3p, CDK1 and CCNB1 in HCC and normal hepatocytes were determined by qRT-PCR and WB. The results showed that LINC00356, CDK1 and CCNB1 were highly expressed in HCC, while miR-199a-3p was lowly expressed. Dual luciferase reporter gene assay, RIP and RNA-pull down assays demonstrated the targeted binding relationship of LINC00346-miR-199a-3p-CDK1 /CCNB1. Overexpressing LINC00460 and silencing miR-199a-3p promoted cell invasion, inhibited apoptosis of HCC, and arrested the cell cycle in S phase while opposite results were obtained when silencing LINC00346, CDK1, and CCNB1. LINC00346 indirectly affects liver cancer by promoting the expression of CDK1 / CCNB1 through competitive adsorption of miR-199a-3p. In addition, the study also demonstrated that overexpression of LINC00346 indirectly inhibited the expression of p53 and p21 proteins by promoting CDK1/CCNB1 expressions, thereby blocking the p53 signaling pathway. These results proved that LINC00346 could regulate the expression of CDK1/CCNB1 through the competitive adsorption of miR-199a-3p, thereby affecting the p53 signaling pathway and finally regulating the apoptosis, invasion and cell cycle of HCC cells. In conclusion, LINC00346 can be used as a tumor promoter and potential therapeutic target for HCC metastasis and prognosis.